Association of Infant and Young Child Feeding (IYCF) Practices and History of Infectious Diseases with Nutritional Status Based on Weight-for-Height Indicators Among Children Aged 24–59 Months in the Wates Community Health Center Working Area, Central Lampung Regency, 2026 - Hurul Aini; Masayu Dian Khairani; Putri Rahma Alamsyah; Linda Puspita Sari (Jurnal EduHealth, 2026)
Wasting is an acute nutritional problem that significantly increases the risk of childhood morbidity and mortality. Given that suboptimal Infant and Young Child Feeding (IYCF) practices and infectious diseases are major contributing factors, this study aimed to evaluate their specific associations with the nutritional status of children aged 24–59 months. A case-control study was conducted in the Wates Community Health Center Working Area, Central Lampung Regency, in 2026, involving 62 children (31 wasted cases and 31 non-wasted controls). Nutritional status was assessed using weight-for-height indicators, while variables were collected through structured interviews and anthropometric measurements. Data analysis utilized the chi-square test and Odds Ratios (OR). The results demonstrated a striking disparity: 100% of the wasted children experienced inappropriate IYCF practices, whereas 87.1% of the non-wasted children received appropriate feeding. Statistical analysis revealed that appropriate IYCF practices acted as a substantial protective factor against wasting (p = 0.0001; OR = 0.114). Similarly, a history of infectious diseases was highly prevalent in the case group (87.1%), whereas the absence of infection in the control group (83.9%) was significantly protective (p = 0.0001; OR = 0.028). In conclusion, inappropriate IYCF practices and recurrent infections synergistically drive acute malnutrition. These findings highlight the urgent need for targeted nutritional interventions, particularly during the 6-month complementary feeding transition, coupled with contextual environmental infection control.